Current controversies in the use of aspirin and ticagrelor for the treatment of thrombotic events. (1st December 2016) - Myat, Aung; Tantry, Udaya S.; Kubica, Jacek; Gurbel, Paul A.
ABSTRACT: Introduction : A P2Y12 inhibitor plus aspirin is the most widely used antiplatelet strategy to prevent adverse outcomes in the setting of atherothrombotic vascular disease. Areas c overed : A paucity of robust evidence for an optimal dose, gastrointestinal toxicity, ineffectiveness in high-risk patients and interactions with other antiplatelet agents, are major controversies associated with aspirin therapy. Ticagrelor is a reversibly binding oral P2Y12 receptor blocker that mediates potent inhibition of adenosine diphosphate-induced platelet function. It is more effective than clopidogrel in preventing thrombotic events in acute coronary syndrome patients. The absence of a beneficial effect for ticagrelor versus clopidogrel in ACS observed in the North American subgroup of the PLATelet inhibition and patient Outcomes (PLATO) trial has been attributed to a higher concomitant aspirin dose. Expert c ommentary : Ongoing studies are now investigating the plausibility of removing aspirin therapy in the setting of potent P2Y12 receptor blockade via ticagrelor monotherapy or replacing aspirin with an oral anticoagulant.